Piezoelectric Polarization and Empty Conduction Band of Zinc Sulfide: Structure Modulation on Graphitic Carbon Nitride for Carbon Dioxide Reduction to Methane. Issue 11 (5th September 2022) - Hu, Cheng; Sun, Hao‐Yu; Jia, Xue‐Mei; Lin, Hai‐Li; Cao, Jing; Chen, Shi‐Fu
Abstract: Rapid recombination of photoinduced charges on the surface and in the bulk phase of semiconductors severely hinders the photocatalytic performance. The synchronous regulation of photocarriers at different locations is also a huge challenge. With these issues in mind, the simultaneous enhancement of surface and bulk carrier separation of g‐C3 N4 for highly selective reduction of CO2 to CH4 by coupling with dual functional ZnS is reported. The introduction of ZnS not only acts as a cocatalyst to capture the photogenerated electrons of g‐C3 N4, but also forms a polarization electric field to drive the prompt migration and separation of photogenerated charges from bulk to surface. Under concurrent vibration and visible‐light irradiation, the as‐obtained ZnS/g‐C3 N4 demonstrates significantly enhanced piezo‐photocatalytic for CO2 reduction, which is higher than that of photocatalytic and piezocatalytic performance, respectively. In addition, the selectivity of the reduction products is enhanced through optimization of the mass ratio of ZnS/g‐C3 N4 . When the ZnS content is increased to 7.95 wt%, high selectivity (95.7 %) of CO2 reduction to CH4 is achieved on ZnS/g‐C3 N4 . This work provides a means to regulate the carrier movement pathway and to enhance charge separation in the bulk phase and on the surface of the semiconductor for selective CO2 conversion. Abstract : The speedy surface and bulk carriers' separation of g‐C3 N4 were simultaneously enhanced by coupling with dual functional ZnS. The as‐obtained ZnS/g‐C3 N4 presented a dramatically‐enhanced piezo‐photocatalytic for highly selective reduction of CO2 to CH4 under vibration assisted visible light irradiation.